1997
DOI: 10.1021/ja963533+
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Ring-Opening Preequilibrium in the Exchange Reactions of Diosmacyclobutanes

Abstract: Variable-temperature 13C NMR does not show any evidence for intramolecular ethylene rotation in 1-13C. The rates of alkene dissociation for the propene (8) and trans-2-butene (7) adducts of Os2(CO)8 have been measured in hydrocarbon solution and compared with the rates of alkene dissociation from the corresponding Os(CO)4(alkene) adducts 6 and 9. The kinetic labilities of propene and trans-2-butene are reversed in the Os2(CO)8(alkene) and Os(CO)4(alkene) systems; propene is replaced 2.5 times faster than trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 56 publications
3
16
1
Order By: Relevance
“…Furthermore, Corey and Noe proposed a (3 + 2) model for the origin of the high enantioselectivty of the dihydroxylation attained by an amine−OsO 4 complex . Although the [2 + 2] mechanism for the reaction of OsO 4 can also rationalize the stereoselectivities caused by chiral ligands, and the rearrangement of the metallaoxetane to a five-membered diolate was also supported by theoretical considerations, , many of recent theoretical and experimental studies that appeared during the course of this study support the (3 + 2) cycloaddition mechanism …”
Section: Introductionsupporting
confidence: 52%
“…Furthermore, Corey and Noe proposed a (3 + 2) model for the origin of the high enantioselectivty of the dihydroxylation attained by an amine−OsO 4 complex . Although the [2 + 2] mechanism for the reaction of OsO 4 can also rationalize the stereoselectivities caused by chiral ligands, and the rearrangement of the metallaoxetane to a five-membered diolate was also supported by theoretical considerations, , many of recent theoretical and experimental studies that appeared during the course of this study support the (3 + 2) cycloaddition mechanism …”
Section: Introductionsupporting
confidence: 52%
“…We then examined the trans-olefination. Norton et al previously revealed that the reversible trans-olefination of the diosmacyclobutane complex Os 2 (μ-η 1 :η 1 -C 2 H 4 )(CO) 8 proceeds in a stereoretentive manner 36 , 37 . Our group also reported that the trans-olefination of the μ-η 3 :η 3 -1,3,5-triene Pd 2 adduct with a linear 1,3,5-triene proceeds in a stereoretentive manner 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous experimental work has suggested that such organometallic cycloaddition reactions are concerted and stereospecific, [21] and several theoretical studies support this postulate.…”
Section: (3)mentioning
confidence: 91%
“…Previous experimental work has suggested that such organometallic cycloaddition reactions are concerted and stereospecific, [21] and several theoretical studies support this postulate. [22] However, we see no economical way to explain our unusual observations by assuming that the imido ± allene cycloadditions are concerted processes.…”
Section: Zrmentioning
confidence: 96%